Ocenjevanje v vrtcu - Fekonja Peklaj, Urška (Sodobna pedagogika, 2008)
The purpose of the article is to present and critically assess different possibilities and methods of assessing the baheviour of children in kindergarten by teachers, parents and psychologists. Since in the period of infant and early childhood, development is the very fast in many fields and because there are large individual differences in development between children of the same age, it is very demanding to monitor children in the pre-school education process. Kindergarten teachers can use different methods and techniques (e.g. observation in a natural situation, compilation of a personal file for a child, structured questionnaires) with which they can assess the behaviour of an individual chil in kindergarten as objectively and validly as possible. Many authors include assessments of the child's behaviours given by kindergarten teachers in their surveys as one of the criteria of the child's development which holds large significance for the interpretation and understanding of the child's achievements in standardised development.
Keywords: ocenjevanje; predšolska vzgoja; predšolski otroci; otroški vrtci; otroška psihologija